Inquiry-based Learning Approach in Physical Education: Stimulating and Engaging Students in Physical and Cognitive Learning. Issue 2 (12th February 2016) - Østergaard, Lars Domino
Abstract : Inquiry is an approach that promotes engagement, motivation and learning, and which involves use of cognitive knowledge, bodily experience and communicative skills. Usually the inquiry method with skills like observations, planning, investigations, experimenting and drawing conclusions is related to natural sciences, but this paper describes an inquiry-based learning approach used in physical education teacher education. The first phase in inquiry work is to discuss and reflect on a given question or challenge which is realistic and relevant for the students. In the described example, the challenges were how it was possible in a given sports arena to modify or create a ball game for lower secondary students (grade 8) to fulfill three distinctive curriculum-related goals (selected by the student teacher). In the next phases the students in groups were to discuss, argue and formulate predictions of how to deal with the challenge, and then by using the inquiry skills mentioned above they were to investigate, test and collect data to confirm or disapprove their prediction. Together with the other students they finally played their game and discussed, concluded and criticized their findings in relation to the prediction. Based on observations of and interviews with students who have been taught by means of the inquiry method it is apparent that the students, besides enhancing their motivation and engagement in physical education teacher education, also enhanced both physical and cognitive learning by using bodily experiences, cognitive knowledge, communicative skills and inquiry-based skills.